(untitled) (The Planet, 2024)
Introduction: Chronic Kidney Disease (CKD) is a growing global health concern with complex metabolic implications, including alterations in serum magnesium levels. This study aims to explore the relationship between serum magnesium levels and different stages of CKD, as well as the impact of the duration of illness on this relationship. Methods & materials: This cross-sectional study was conducted on 220 patients admitted to the Department of Nephrology and Medicine, Rajshahi Medical College Hospital, Rajshahi, Bangladesh. Data were collected on demographic variables, CKD stages, and biochemical parameters, including serum magnesium levels. The duration of illness was also recorded and analyzed. Result: The mean age of the study population was 52.89±10.42 years, with a male predominance (63.6%). A high prevalence of advanced CKD stages was observed, with 67.28% of participants in either Stage 4 or Stage 5. A significant negative correlation was found between serum magnesium levels and estimated Glomerular Filtration Rate (eGFR) (r=-0.735, p<0.01). Additionally, a positive association was identified between the duration of illness (12 to 36 months in 65.45% of participants) and advanced CKD stages. Conclusion: The study reveals a complex interplay between serum magnesium levels, eGFR, and the duration of illness in CKD patients. The high prevalence of advanced CKD stages and its association with longer duration of illness underscore the need for timely diagnosis and effective early intervention strategies. Monitoring serum magnesium levels could be instrumental in the comprehensive management of CKD patients.